PENGARUH SALES PROMOTION APLIKASI TIKTOK, ONLINE COSTUMER REVIEW DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA PENGGUNA TOKOPEDIA : (MAHASISWA FEBI 2021 UIN SAYYID ALI RAHMATULLAH TULUNGAGUNG) - Maghfirotul Hasanah, Fadila; Priantilianingtiasari, Ruly (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
Current technological developments have made a shift in behavior in consuming a product from offline to online, this is marked by the development of e-commerce which has increased significantly Increasing online sales requires several things, one of which is sales promotion for the TikTok application, online customer reviews, and prices which have recently received attention from the business community and academics in relation to purchasing decisions. This study aims to determine the effect of the TikTok application sales promotion on purchasing decisions, the effect of online customer reviews on purchasing decisions, the effect of price on purchasing decisions and to determine the effect of TikTok application sales promotion, online customer reviews and prices simultaneously on purchasing decisions. The approach used is associative quantitative research, with Tokopedia and TikTok users as the population, with the number of Fakultas Ekonomi dan Bisnis Islam 2021 students at Universitas Islam Negri Sayyid Ali Rahmatullah Tulungagung of 3.537 students who are the population in this study, using the Slovin formula as the basis for taking the number of samples, namely 392 using the probability sampling technique and data collection using a questionnaire with a Likert measurement scale. The data were processed using SPSS version 22 through multiple linear regression. With the results of the TikTok application sales promotion research that has a significant effect on purchasing decisions, online customer reviews have a significant effect on purchasing decisions, prices have a significant effect on purchasing decisions and simultaneously TikTok application sales promotion, online customer reviews and prices have a significant effect on purchasing decisions.